2011
DOI: 10.1063/1.3549691
|View full text |Cite
|
Sign up to set email alerts
|

Strain dependence of thermal conductivity of [0001]-oriented GaN nanowires

Abstract: The thermomechanical behavior of ͓0001͔-oriented GaN nanowires with 2.26 and 3.55 nm in diameter under tensile loading is analyzed using molecular dynamics simulations with the Green-Kubo method and quantum correction. A phase transformation from wurtzite to a tetragonal structure is observed. The thermal conductivity is found to decrease as the wires undergo tensile deformation and phase transformation, except for the smallest diameter and temperatures above 1495 K at which it remains largely constant as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The thermal conductivity of the TS-structured nanowires with a strain of 0.1 is 4.2 W/mK which is 27% lower than that of the unstressed WZ nanowires. The decrease in conductivity is attributed to the strain of the wire and a higher disorder in the surface of the TS-structured wires than that of the WZ-structured wire, 17 as illustrated in Fig. 3.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The thermal conductivity of the TS-structured nanowires with a strain of 0.1 is 4.2 W/mK which is 27% lower than that of the unstressed WZ nanowires. The decrease in conductivity is attributed to the strain of the wire and a higher disorder in the surface of the TS-structured wires than that of the WZ-structured wire, 17 as illustrated in Fig. 3.…”
Section: Resultsmentioning
confidence: 96%
“…15,16 Thermal conductivity of the ZnO nanowires increases during the transformation from WZ to HX because the density of the HX structure is higher than that of the WZ structure. 16 In our previous work, 17 a phase transformation from WZ to TS structure is shown to occur in [0001]-oriented GaN nanowires under tensile loading. In contrast to what is observed in the ½01 10-oriented ZnO nanowires, the phase transformation from WZ to TS lowers the thermal conductivity of the GaN nanowires.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies had been carried out to monitor the phonon thermal conductivity in stressed GaN nanostructures [9e11]. For example, Junk et al adopted the molecular dynamics method to simulate the strain-dependent thermal conductivity in GaN nanowires, and they revealed that the deformation along the axial direction reduces the thermal conductivity for GaN nanowires with different shape of cross section [9]. Zhu and Ruan also investigated the relationship between the stress fields and the phonon thermal conductivity of GaN nanofilms and GaN nanowires [11].…”
Section: Introductionmentioning
confidence: 99%